Polydopamine-doped virus-like mesoporous silica coated reduced graphene oxide nanosheets for chemo-photothermal synergetic therapy. (July 2020) - Liao, Jieying; Zhang, Huicong; Wang, Xuandong
Multifunctional nanocarriers have been widely accepted and utilized for biomedical applications, because of their structural regularity, convenient post-modification and controllable structure and morphology. Herein, we reported polydopamine-doped virus-like mesoporous silica coated reduced graphene oxide nanosheets (rGO@PVMSNs) nanocomposites by a facile oil–water biphase stratification method. The synthesized rGO@PVMSNs nanocomposites performed excellent biocompatibility and photothermal performance. They could be employed as photoacoustic imaging contrast in vivo. Furthermore, the rGO@PVMSNs nanocarriers were used for loading the antitumor drug doxorubicin (DOX), the rGO@PVMSNs@DOX nanocomposites were also demonstrated to be with high inhibition of HepG2 cancer cells, especially with the help of near-infrared irradiation, which were more efficient than single chemotherapy or photothermal therapy. The rGO@PVMSNs@DOX nanocomposites of this work could be used as photoacoustic imaging and chemo-photothermal synergetic therapy agents, which show a new perspective for clinical tumor diagnosis and therapy.